067 Metformin in insulin resistant LV dysfunction, a double-blind, placebo controlled trial (Tayside trial). (22nd September 2015) - Wong, A K F; Symon, R; ADZjali, M; Ang, D; Choy, A M; Petrie, J R; Struthers, A D; Lang, C C
Abstract : Introduction: Chronic heart failure (CHF) is increasingly recognised as an insulin resistant state and the degree of insulin resistance (IR) has been shown to correlate with disease severity and clinical outcome. However, these association studies do not distinguish between cause and effect. It is not certain if IR is merely a marker reflecting the severity of disease in CHF or if it is the culprit in the pathogenesis of CHF. If it is a culprit that worsens CHF, improving it may lead to better clinical outcome. Aims: The purpose of our study was to determine if reversing IR in non-diabetic CHF patients results in clinical benefits. Methods and Results: In a double-blind, placebo controlled trial, 62 non-diabetic insulin resistant CHF patients (mean age, 65.2±8.0 yrs; male, 90%; LVEF, 32.6±8.3%; NHYYA I/II/III/IV 11/45/6/0) were randomised to receive 4 months of either metformin (n=39, 2 g per day) or matching placebo (n=23). IR was defined by Fasting Insulin Resistance Index (FIRI) of ≥2.7. Cardiac-pulmonary exercise testing, echocardiography, flow mediated dilatation, EndoPAT (a measurement of endothelial dysfunction), 6-minute walk test, Minnesota Living with Heart Failure Questionnaire, anthropometric measurements, FIRI and biomarkers were assessed at baseline and after 4 months of intervention. Compared to placebo, metformin decreased FIRI (from 5.8±3.8 to 4.0±2.5, p<.001), decreased fasting glucose (from 5.6±0.6 to 5.2±0.4 mmol/L, p=0.005), reduced fasting insulin (from 26.8±14.3 to 20.2±10.4 mU/L, p<.001), reduced serum HbA1c (from 5.7±0.3% to 5.5±0.3%, p=.002), decreased serum leptin (from 16.6±23.3 to 12.1±16.5 ng/ml, p<0.05) and resulted in a weight loss of 1.9 kg (p<.001). Metformin treatment significantly improved NYHA functional class (from 1.89±0.5 to 1.75±0.5, p=0.046). Although peak exercise parameters and endothelial function did not differ between treatment groups, sub-maximal parameters were significantly improved with metformin therapy, notably VE/VCO2 slope (from 32.9±15.9 to 28.1±8.8, p=0.05) and ventilatory class (from 1.90±0.9 to 1.5±0.9, p=0.021). Conclusion: This novel study provides supportive evidence that metformin is a safe treatment in non-diabetic CHF which improves glucose homeostasis but more importantly, results in significant improvement in NHYA class, VE/VCO2 slope and ventilatory class, all of which are important prognostic markers in CHF. Reversing IR may represent a new therapeutic strategy in CHF.